Effect of exercise on abdominal fat loss in men and women with and without type 2 diabetes. Issue 11 (25th November 2013) - Dobrosielski, Devon A; Barone Gibbs, Bethany; Chaudhari, Sameer; Ouyang, Pamela; Silber, Harry A; Stewart, Kerry J
Abstract : Objective: To examine the effect of exercise on abdominal adipose tissue in adults with and without type 2 diabetes mellitus (T2DM). Design: Post hoc analysis of two randomised controlled trials. Setting: Outpatient secondary prevention programme in Baltimore, Maryland, USA. Participants: 97 men and women with prehypertension, stage 1 or medically controlled hypertension. 49% of the sample was also diagnosed with T2DM. Intervention: All participants completed a 26-week (6.5 months) supervised aerobic and resistance exercise programme following American College of Sports Medicine guidelines. Primary and secondary outcome measures: The main outcomes in this post hoc analysis were total abdominal adipose tissue (TAT), subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT) measured by MRI. Secondary outcomes were to determine whether the magnitude of abdominal fat change differed by diabetes status in men and women and to identify the predictors of change in abdominal fat distribution with exercise. Results: Overall, participants (mean age 61±6 years; 45% women) significantly improved peak oxygen uptake by 15% (p<0.01) and reduced weight by 2% (p<0.01). No change in SAT was observed after training. The reduction in VAT following exercise was attenuated in participants with T2DM (–3%) compared with participants who were non-T2DM (–18%, p<0.001 for the difference in change). The magnitude of VAT loss was associated with a decrease in body weight (r=0.50, p<0.001). After adjustment for weight change using regression analysis, diabetes status remained an independent predictor of the change in VAT. Conclusions: Although participants with and without T2DM attained an exercise training effect as evidenced by increased fitness, VAT was unchanged in T2DM compared to those without T2DM, suggesting that these individuals may be resistant to this important benefit of exercise. The strategies for reducing cardiovascular disease risk in T2DM may be most effective when they include a weight loss component. Clinical Trials Registration: Clinicaltrials.gov Registry NCT00212303 .